WATSON'S CATEGORIES ANALYSIS OF SEQUENCES AND SERIES QUESTION - Anggita Maharani; Ika Wahyuni; Cucu Oktavianingsih (IKIP Siliwangi and I-MES, 2020)
This article contains students' answers to the row and series questions which are then analyzed based on the Watson category. The problem that often arises is a large number of students who still cannot give the right answer to the sequence and sequence problems. Analysis very important to do, especially on the wrong answers so that the teacher knows where the student lies in solving a problem so the teacher can take appropriate corrective action. The Watson category is used to facilitate the tracking of errors that are often made by students. This paper describes the types of errors in solving row and series problems based on the Watson category and describes the percentage of each type of error. This type of research is a descriptive study with a qualitative approach. This research was conducted by giving a test about sequences and series question in the form of a description of four questions. The results showed that there were two categories based on Watson which were dominantly carried out by students, namely 1) incorrect procedures (34.06%) and 2) conclusions were lost (20.33%).